Comparative analysis of the efficacy of angiotensin II receptor blockers for uric acid level change in asymptomatic hyperuricaemia. (1st August 2020) - Kim, Hun‐Sung; Kim, Hyunah; Lee, Sue Hyun; Kim, Ju Han
Abstract: What is known and objective: There is much controversy over how angiotensin II receptor blockers (ARB) or angiotensin‐converting enzyme inhibitors (ACEI) affect blood uric acid levels. Though ARB is not used to lorcwer the uric acid concentration in the blood, losartan, one of the ARB series, is known to reduce the uric acid concentration in the blood and is a preferred drug for hypertensive patients with gout. However, there is no clear conclusive consideration which ARB should be selected for the patients who have simply increased uric acid concentration, other than gout patients. This research aims to compare the variations of the uric acid concentration in the blood in accordance with the prescription of ACEI or ARB targeting patients who were not diagnosed with gout. Methods: This research was conducted on the patients who were, for the first time, prescribed ACEI or ARB for a total of 7 years from January 2009 to December 2015. This study has extracted the uric acid values after between 60 days and 120 days (average 90 days, defined as Visit 1) on the basis of the first prescription date of ACEI or ARB. Results and discussion: In this study, ACEI was 17.0% of usage (3787/22 293 patients) and ARB was 83.0% (18 506/22 293 patients). Unlike ACEI (5.91 ± 0.03 vs 5.86 ± 0.03 mg/dL, P  = .059), ARB showed a statistically significant decrease after 3 months (5.71 ± 0.01 vs 5.69 ± 0.01 mg/dL, P  = .023). In the case of irbesartan (n = 1530, 6.13 ± 0.06 mg/dL vs 5.89 ± 0.05 mg/dL, P  < .001) and olmesartan (n = 2719, 5.70 ± 0.04 mg/dL vs 5.63 ± 0.03 mg/dL, P  = .008), the decrease in the uric acid after 3 months was revealed as statistically significant. In elderly aged over 60 years, only irbesartan (n = 855, 5.75 ± 0.07 mg/dL vs 5.59 ± 0.07 mg/dL, P  = .006) showed a significant decrease in the uric. When the eGFR was less than 60 mL/min/1.73 m 2, both ACEI (n = 1108, 6.95 ± 0.07 mg/dL vs 6.73 ± 0.07 mg/dL, P  = .001) and ARB (n = 5280, 6.88 ± 0.03 vs 6.60 mg/dL ± 0.03 mg/dL, P  < .001) showed a significant decrease in the uric acid. What is new and conclusion: Although all types of ACEIs and ARBs are being prescribed with similar purposes, ARB (or ACEI) medication does not have a class effect and has varying effects on uric acid levels. The decreases in uric acid levels were relatively small. ARBs seem to be more advantageous than ACEIs for hyperuricaemia patients without gout who are aiming to maintain uric acid decrease levels. Furthermore, irbesartan can be a good substitute for losartan in view of the fact that at least the uric acid level is not increased. Abstract : Change in uric acid level according to various ARBs from baseline to 3 months.